Colorectal metastasis to the gallbladder mimicking a primary gallbladder malignancy: histopathological and molecular characteristics. Issue 3 (18th July 2019) - de Bitter, Tessa J J; van der Linden, Ragna L A; van Vliet, Shannon; Weren, Fieke; Sie, Daoud; Ylstra, Bauke; van der Linden, Hans C; Knijn, Nikki; Ligtenberg, Marjolijn J L; van der Post, Rachel S; Simmer, Femke; Nagtegaal, Iris D
Abstract : Aims: Outcomes of colorectal cancer (CRC) treatment and survival have steadily improved during the past decades, accompanied by an increased risk of developing second primary tumours and metastatic tumours at unusual sites. Metastatic CRC can show mucosal colonisation, thereby mimicking a second primary tumour. This potential confusion could lead to incorrect diagnosis and consequently inadequate treatment of the patient. The aim of this study was to differentiate between metastatic CRC and a second primary (gallbladder cancer, GBC) using a combination of standard histopathology and molecular techniques. Methods and results: Ten consecutive patients with both CRC and GBC were identified in our region using the Dutch National Pathology Archive (PALGA). Two patients served as negative controls. Histology of GBC was reviewed by nine pathologists. A combination of immunohistochemistry, microsatellite analysis, genomewide DNA copy number analysis and targeted somatic mutation analysis was used to aid in differential diagnosis. In two patients, CRC and GBC were clonally related, as confirmed by somatic mutation analysis. For one case, this was confirmed by genomewide DNA copy number analysis. However, in both cases, pathologists initially considered the GBC as a second primary tumour. Conclusions: Metastatic CRC displaying mucosal colonisation is often misinterpreted as a second primary tumour. A combination of traditional histopathology and molecular techniques improves this interpretation, and lowers the risk of inadequate treatment.